Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1980
DOI: 10.1098/rspa.1980.0043
|View full text |Cite
|
Sign up to set email alerts
|

Grain boundary segregation and intergranular fracture in molybdenum

Abstract: The refractory group VIA metals generally exhibit intergranular brittleness when they are in the recrystallized condition. This causes severe problems in their fabrication and places major limitations on their practical application. The phenomenon, generally referred to as recrystallization embrittlement, results in large increases in the ductile-to-brittle transition temperature and a change in fracture mode in the lower shelf regime from cleavage to intergranular with a significant decrease in ductility. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(31 citation statements)
references
References 17 publications
2
29
0
Order By: Relevance
“…Especially, oxygen segregation weakens the grain boundaries. 6,11,12 On the other hand, it is believed that the embrittlement is an intrinsic property of molybdenum. 7,8,32 Intergranular fractures occur more often in microstructures with many random high-angle grain boundaries.…”
Section: Recrystallized Molybdenum In the Charpy Impact Testmentioning
confidence: 99%
See 2 more Smart Citations
“…Especially, oxygen segregation weakens the grain boundaries. 6,11,12 On the other hand, it is believed that the embrittlement is an intrinsic property of molybdenum. 7,8,32 Intergranular fractures occur more often in microstructures with many random high-angle grain boundaries.…”
Section: Recrystallized Molybdenum In the Charpy Impact Testmentioning
confidence: 99%
“…[4][5][6][7][8][9] Nevertheless, recrystallization annealing of the as-deformed and stress-relieved condition of molybdenum leads to a significant increase of the DBTT and even more to intergranular embrittlement, which is believed to be caused by the larger grain size and segregation enrichments at the grain boundaries. [4][5][6][10][11][12][13] Recent atom probe investigations revealed phosphor, nitrogen and oxygen impurities at the grain boundaries of technically pure molybdenum 14,15 of which especially segregated oxygen is assumed to promote intergranular failure. 6,11,12 By adding small amounts of carbon and boron, the ductility of molybdenum can be improved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the fracture strength of molybdenum depends strongly on factors such as grain boundary character and impurity segregation. Kumar and Eyre [12] demonstrated that under certain conditions, extremely small amounts of oxygen (about 6 ppm) could cause grain-boundary embrittlement.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] A small amount of carbon can significantly enhance the fracture strength of pure molybdenum, and consequently, its ductility. The latter effect is characterized by the relative decreasing in the ductile-to-brittle transition temperature (DBTT).…”
Section: Introductionmentioning
confidence: 99%